2004
DOI: 10.1080/00071660412331286244
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod and oviposition time in broiler breeders

Abstract: 1. Oviposition times were recorded for broiler breeder hens under 8-, 10-, 11-, 12-, 13-, 14- and 16-h photoperiods. 2. Mean oviposition time (MOT) was delayed relative to dawn by approximately 0.5 h for each 1-h increase in photoperiod up to 14 h, but was similar for 14- and 16-h photoperiods. However, the 0.5 h/h regression for the time when half the eggs were laid continued through to 16 h. 3. The rate of change in MOT for each 1-h increase in < or = 14-h photoperiod was similar to that reported for early a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 4 publications
5
20
0
1
Order By: Relevance
“…The number of eggs laid at each collection time was influenced by genotype (Table 1), which coincides with findings of Lillpers and Wilhelmson (1993), Garces and Casey (2003) or Lewis et al (2004), who described differences in the mean oviposition time according to genotype. Plymouth Rock hens laid more eggs early in the morning (until 6:00) whereas in Blue strain and F1 genotypes the time of oviposition at 6:00 and 10:00 was similar.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The number of eggs laid at each collection time was influenced by genotype (Table 1), which coincides with findings of Lillpers and Wilhelmson (1993), Garces and Casey (2003) or Lewis et al (2004), who described differences in the mean oviposition time according to genotype. Plymouth Rock hens laid more eggs early in the morning (until 6:00) whereas in Blue strain and F1 genotypes the time of oviposition at 6:00 and 10:00 was similar.…”
Section: Resultssupporting
confidence: 68%
“…Lewis et al (1995) revealed that the mean oviposition time for a brown egg hybrid was 1.2 to 1.4 h earlier than that of a white egg genotype. In the next paper Lewis et al (2004) recorded the time of oviposition in broiler breeder hens under an 8-16 h photoperiod. The mean oviposition time was delayed in a photoperiod up 14 h but it was similar for a 14 h and 16 h photoperiod.…”
mentioning
confidence: 99%
“…All these events are influenced by the age of bird, the strain, level of nutrition, and other environmental factors Gous 2006, 2007). Lewis et al (2004) reported that in commercial crossbred laying hens the mean oviposition time was by about 1 h earlier in comparison with broiler breeders. Zakaria et al (2005) reported that as a flock was ageing, the eggs were laid later in the day.…”
Section: Introductionmentioning
confidence: 99%
“…There are few published data about the time pattern of oviposition in broiler breeder hens. Recently, Lewis et al (2004) recorded the mean oviposition time for in-lay birds kept under different photoperiod conditions (8 h-16 h light) and revealed differences in oviposition time between Some researchers demonstrated a relationship between egg position in the sequence and hatchability of eggs from broiler breeder hens (Robinson et al, 1991a;Fasenko et al, 1992). However, Zakaria et al (2005Zakaria et al ( , 2009 reported no effect of oviposition time on hatchability of fertile eggs.…”
mentioning
confidence: 99%